Is Aid Unfriendly to Tax? African Evidence of Heterogeneous Direct and Indirect Effects - (:unkn) unknown (My University, 2016)
We explore the heterogeneous effects together with the transmission channels of aid on tax revenues in 47 African countries over 1990-2011 using a panel smooth threshold regression model and two alternative tax datasets from IMF and ICTD. We find that aid enhances tax revenues with decreasing returns for a threshold of 6.3% and 23% of GNI for total taxes and non-resource taxes respectively. Aid effect varies across countries and over time, but, on average, is positive. Moreover, we evidence that aid conditions the impact of the level of development, trade, institutions and resource wealth on tax.
Keywords: African Research